CsI(TI) films: deposition, examination of structure and scintillation - Lebedinsky, A.; Fedorov, A.; Ananenko, A.; Mateychenko, P. (Functional Materials, 2007)
The sublimation of the bulk CsI crystal with optimal activator concentration istead of powder source use at vacuum deposition of CsI(TI) films has been shown to provide CsI(TI) films with required content and uniform distribution of activator in the film volume. The CsI(TI) film produced by this technology demonstrate superior scintillation characteristics in comparison with CsI(TI) film deposited by a usual technology. The dependence of the film crystalline structure on the deposition conditions has been studied in detail.